Letter (copy) : Goods for Spain - Tewson, Vincent
032-0203-001 International. HVT/EAB/AT/144 4th November, 1938. Mr. E. Winstanley, Co-operative Wholesale Society Ltd., 1 Balloon Street, Manchester, 4. Dear Mr. Winstanley, GOODS FOR SPAIN In accordance with your request over the telephone this afternoon, we are returning herewith your invoices relating to the consignment of children's sandals, which were included in the consignment of goods to Spain, shipped by your C.W.S. Progress. We understand you wish to make some amendments regarding the charges for packing. Yours sincerely, Assistant Secretary. Enc. 292/946/32/203